Numeracy Literacy in Early Childhood: An Investigation in Arithmetic, Geometry and Patterns in Early Stage - Nur, Iyan Rosita Dewi; Herman, Tatang; Dahlan, Tina Hayati (Universitas Muhammadiyah Mataram, 2022)
Early childhood education is a coaching effort carried out for children from birth to the age of six by providing educational stimuli in helping their physical and spiritual growth and development with the aim that children have maximum readiness to enter higher education levels. Numerical literacy in early childhood can be used as a tool used in developing thinking skills in children, supporting children in developing various talents or intellectual potentials they have and can be used as a means of cultivating a positive affective side in instilling basic personalityThis study aims to describe a numeracy literacy skills in early childhood students. The research method used is descriptive qualitative. Researchers used purposive sampling to take research subjects, and obtained as many as 28 PAUD students, and from 28 people 3 people were taken to be analyzed in depth related to their numeracy literacy skills. Instruments in this research are observation, test, Interview, and dokumentation. Data analysis techniques in this study include data reduction, data presentation, and conclusions. The results of research that have been done show that numeracy literacy in early childhood aged 5-6 years of arithmetic, geometry and patterns as follows: (1) Be able to name the symbols of numbers 1-20, (2) Have the ability to using number symbols to calculate, (3) Able to match numbers with number symbols and recognize differences based on